2013
DOI: 10.1111/trf.12126
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative cell salvage is associated with reduced postoperative blood loss and transfusion requirements in cardiac surgery: a cohort study

Abstract: The use of cell salvage throughout the entire procedure reduces postoperative blood loss and allogeneic RBC transfusion. These findings advocate implementation of cell salvage in all patients undergoing on-pump cardiac surgery, irrespective of anticipated surgery-related blood loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
2
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 31 publications
2
43
2
5
Order By: Relevance
“…The decreased risk of perioperative pRBC transfusions found in patients who received ICS in our study compared favourably to findings from certain previously published studies 8,12,[14][15][16]19,22 but differed from others where either no change 7,9,13,18 or an increase in perioperative pRBC transfusion rates 17 was noted with the use of ICS. With respect to coagulation product transfusion, to our knowledge, the present study is the first to have shown a decrease in coagulation product transfusion with the use of ICS.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…The decreased risk of perioperative pRBC transfusions found in patients who received ICS in our study compared favourably to findings from certain previously published studies 8,12,[14][15][16]19,22 but differed from others where either no change 7,9,13,18 or an increase in perioperative pRBC transfusion rates 17 was noted with the use of ICS. With respect to coagulation product transfusion, to our knowledge, the present study is the first to have shown a decrease in coagulation product transfusion with the use of ICS.…”
Section: Discussionsupporting
confidence: 74%
“…Of those that did, it appears that the processing of residual CPB contents was associated with a significant decrease in pRBC transfusion 12,14,15,19,22 and a decrease in postoperative chest tube drainage. 19 The beneficial effect of ICS seen when processing residual CPB contents may result, in part, from the removal of excess heparin 23 or an accumulation of inflammatory mediators commonly associated with CPB. 24 We demonstrated an average cost savings of $116 per patient for whom ICS was used.…”
Section: Icsmentioning
confidence: 99%
See 1 more Smart Citation
“…71 However, postoperative platelet counts two hours after CPB are the same between control and cell-salvaged patients, although postoperative blood loss was less in patients who had received cell-salvaged blood. 72 Further work is required to elucidate the pattern of PMV activity during cardiac surgery and the potential impact on perioperative coagulation.…”
Section: Cell Salvagementioning
confidence: 99%
“…Intraoperative cell salvage (IOCS) is commonly being used in cardiac, orthopaedic and vascular surgery with reduction of allogeneic blood transfusion (Ashworth & Klein, 2010;Vonk et al, 2013) with increasing use in obstetrics (Liumbruno et al, 2012). A survey of UK maternity units in [2005][2006] showed that around 40% of centres were using cell salvage, with lack of training and availability of equipment being barriers to its use (Teig et al, 2007;RCOG, 2009).…”
Section: Cell Salvagementioning
confidence: 99%